Towards malum prohibitum: crime deterrence strategies for reducing illicit antiquities trade - Koush, Alesia (Crime, law and social change, 2024)
Fight against illegal antiquities trade has predominantly taken a reactive stance. This study operates with novel quantitative and qualitative data obtained through a survey and interviews with 42 law enforcement agents from 21 source and market countries. An empirical insight on illegal antiquities trade is provided, and a comprehensive reference framework of crime deterrence strategies is created. Incidence and efficiency rates of the identified strategies conceal that a law enforcement response at the market side, strengthened through policing, criminal prosecution, reverse of the burden of proof, market control and traceability, is deemed most effective deterrence-wise leveraging certainty of being caught, severity and celerity of punishment, the key mechanisms of Deterrence theory. By contrast, the existing international and EU legislation are considered inconsistent. The findings reveal the need for critically reviewing the current situation and defining a pathway for antiquities markets from malum non prohibitum environments to at least malum prohibitum climates: shaping proactive policy approaches through updated legislation and targeted crime deterrence and prevention activities to be applied mainly at the market side.